Connected Science : Strategies for Integrative Learning in College - Stewart, Joanne L.; Schlegel, Whitney M.; Geelan, David; Ferrett, Tricia A. (Book collections on Project MUSE., 2013)
Informed by the scholarship of teaching and learning (SOTL), Connected Science presents a new approach to college science education for the 21st century. This interdisciplinary approach stresses integrative learning and pedagogies that engage students through open-ended inquiry, compelling real-world questions, and data-rich experiences. Faculty from a variety of disciplines and institutions present case studies based on research in the classroom, offering insights into student learning goals and best practices in curriculum design. Synthetic chapters bring together themes from the case stu.